Analysis of Nutritional Value of Various Loloh in Bali - Wipradnyadewi, Putu Ari Sandhi; Arihantana, Made Indri Hapsari; Wisaniyasa, Ni Wayan (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 3 No 1 (2016), 2016)
The aim of this study is to inventory and find out the nutritional value of various loloh in Bali such as loloh kunyit asam, loloh don sirsak, loloh temulawak, loloh don sirih or base, loloh don jarak, and loloh don beluntas. This study consists of two phases: the first phase is the inventory of loloh such as loloh kunyit asam, loloh don sirsak, loloh temulawak, loloh don sirih or base, loloh don jarak, and loloh don beluntas that is located in Denpasar city. The second phase is the analysis of nutritional value of loloh. The results showed that loloh kunyit asem, loloh temulawak, loloh don jarak, loloh don sirih or base, loloh don beluntas, and loloh don sirsak are traditional Balinese drinks that can be found in Denpasar in a slight amount. The vitamin C contents ranges from 17,10 – 287,50 mg/100 ml, total acid 0,11 – 0,88 %, total sugar 2,84- 7,44 %, and tannin levels are 0,02 – 0,06 %.
Keywords: analysis, nutritional value, loloh